Study on the influence of gear pair operating parameters on heat transfer characteristics of lubrication systems and global sensitivity analysis - Yankun Hou; Yaguo Lyu; Jiaolei Tian; Zhengang Liu (Case Studies in Thermal Engineering)
Given the urgent demand for lightweight design and energy conservation in aviation engines, this study investigates the impact of gear pair operating parameters on the heat transfer characteristics of the lubrication system. By establishing a gear jet lubrication testing platform, the influence of parameters such as gear rotational speed and supply flow rate on the supply-scavenge oil temperature difference, as well as heat generation power, is systematically revealed. Using a Back Propagation (BP) neural network, we developed a nonlinear mapping model that links operating parameters and heat transfer characteristics. Through the application of the Sobol' global sensitivity analysis method, parameters that significantly contribute to heat transfer characteristics are identified. The results indicate that gear rotational speed and supply flow rate, along with their synergistic effects, play a dominant role in determining heat transfer characteristics. A cooling benefit is proposed as a quantitative indicator, and by defining the rate of temperature change resulting from flow variation, a parameter sensitivity threshold decision mechanism is established. This mechanism balances the supply-scavenge oil temperature difference and heat generation power from the perspective of the lubrication system. This study provides a feasible improvement pathway for the lightweight design of lubrication systems.